L1-L2 phonological interference and attitude towards english of ABEL students - Sabado, Benjamin M. (PSU Urdaneta Campus Research Journal, 2015)
This study aimed to determine the L1-L2 Phonological Interference and Attitude towards English of 30 AB English Language students. Specifically, it aimed to answer the profile of the respondents in terms of Mother tongue, high school graduated from and attitude towards the English language. The descriptive-correlational design was used in this study to determine the respondents' rate in committing phonological interference or error. The respondents of this study included AB English Language students enrolled in Pangasinan State University, Urdaneta Campus. To elicit data for the postulated questions, a research-developed questionnaire on Contoids Phonology Test and adapted questionnaire on Language attitude test were used. Results show that the respondents have positive attitude towards the English language. Both groups of speaker have difficulty pronouncing the contoid sounds /z/, /Ɵ/ and /Ʒ/. However, as far as overall performance was concerned, bot Ilocano and Pangasinan speakers were good. Both groups’ rate in committing phonological interference or error was rated “very low”. Profiles of the respondents were also correlated to the instances of phonological interference. From the findings of the study, the following conclusions were drawn: Both groups of speaker have difficulty pronouncing the consonant sounds /z/, /Ɵ/ and /Ʒ/ because of their absence in Iloco and Pangasinan Phonetic System. The respondents are generally characterized as having low commission of phonological interference. The profile of the students is related to the rate of committing phonological interference. The respondents relatively vary in type of high school they graduated from and they have a positive attitude towards English. The following recommendations were also presented: An explicit discussion on the basic rules of pronunciation of consonants. Language Instructors may give tasks regarding pronunciation in a communicative context to let students talk in English more frequently while also improving their pronunciation and articulation. Students may indulge more on activities in phonology, taking those activities more seriously for them to approximate a native-like pronunciation. Language teachers must reinforce students’ motivation towards learning English since students’ attitude is one of the factors that can improve language-learning conditions. Future researchers may consider alternative variables other than those used in this research.